Design And Simulation Of An Optimized Mixed Mode Solar Dryer Integrated With Desiccant Material - Misha, Suhaimi; Ahmed Al-Qadhi, Ahmed Abdullah; Mohd Rosli, Mohd Afzanizam; Akop, Mohd Zaid (IJMME-IJENS, 2017)
Solar drying is one of the methods that have been used since ancient times.This system has been constantly developed in the last few years to acquire better effective results and drying performance.The efficiency of the solar dryer is essentially depends on the thermal distribution and uniformity of flow inside the dryer body.In this paper,a conceptual design of a mixed mode solar dryer which includes direct and forced indirect solar drying integrated with desiccant materials is developed and proposed.Some concepts of this design are new and others are inspired from recent works.Based on these,this mixed mode solar dryer is prospective to be superior in the rate of drying as well as air flow uniformity.Moreover,this improved drier which can be utilized for drying the diverse agricultural products is a simple system and might be manufactured locally.In addition,a simulation of the system using CFD (Computational Fluid Dynamic) software was performed for the optimization of drying chamber configuration by predicting the airflow distribution,temperature and velocity profiles throughout the dryer.This simulation process has the capability to resolve equations of mass conversation,energy and momentum utilizing numerical approach and it is a very useful tool to evaluate the temperature and velocity profiles in the various positions of the system and attain a uniform air flow with higher temperature inside drying cell or chamber. Simulation results are suitable for further validation against an experimental results of the same design.